Contemporary economic geographies - Johns, Jennifer; Hall, Sarah Marie (Bristol bristol University Press, 2025)
The subdiscipline of economic geography has a long and varied history, and recent work has pushed the field to diversify even further. This collection takes this agenda forward by showcasing inspiring, critical and plural perspectives for contemporary economic geographies. Highlighting the contributions of global scholars, the thirty chapters showcase fresh ways of approaching economic geography in research, teaching and praxis.